Poetry and Orality - Senabre, Ricardo (Tropelías: Review of Literary Theory and Comparative Literature, 2019)
The scrupulous respect for the integrity of the texts, the perfectioning of the philological techniques in order to purify and counteract their alterations, have not awakened an analogous concern for the preservation of the reception form which was expected by their authors. During centuries, poetry was conceived and composed to be listened to ―with or without music―, which explains a great part of its formal characteristics and its historical evolution; nevertheless, today is read in silence, and determinate values and functions of the oral nature of the works are frequently left out. In these pages, proof of the survival of this orality and examples of its influence on the composition techniques of the verse are offered.
Keywords: Poetry; orality; philology